Integrasi Layanan Psikologi dalam Program Posyandu Keluarga: Upaya Deteksi dan Penanganan Kecemasan Prenatal di Puskesmas GA - Ayu Septi Pryllia Sukmaputri; Diah Sofiah (Journal of Innovative and Creativity, 2025)
ABSTRACT The study purpose was to examine prenatal anxiety among pregnant women in the Posyandu Keluarga (Family Health Post) community at Puskesmas GA and to implement a psychoeducational intervention aimed at reducing anxiety and strengthening social support. This community-based psychological service was designed to identify psychological issues during pregnancy, especially anxiety related to childbirth, physical health, and emotional adjustment, through assessment and preventive intervention at the primary healthcare level. Materials and methods. The study applied mixed qualitative and quantitative approaches involving interviews, observations, and psychological screenings using the Perinatal Anxiety Screening Scale (PASS) and the Multidimensional Scale of Perceived Social Support (MPSS). Participants included ten pregnant women aged 25–37 years. Data were analyzed through correlation testing (Pearson) and pre–post comparisons using paired sample t-tests to measure intervention effectiveness. Results. The findings revealed that 80% of participants experienced high prenatal anxiety levels, while 60% reported moderate perceived social support. Statistical analysis indicated a significant negative correlation between social support and anxiety (r = -0.671, p = 0.034), meaning higher social support was associated with lower anxiety. After the psychoeducational and relaxation training intervention, there was a significant reduction in prenatal anxiety scores (t = 5.568, p = 0.000) and a notable improvement in participants’ understanding of maternal mental health (Cohen’s d = 2.872). Conclusions. Psychoeducation focusing on prenatal anxiety, the importance of emotional support, and relaxation breathing techniques effectively reduced anxiety levels among pregnant women in the community. Strengthening family and spousal support, integrating cadres’ roles in early detection, and collaboration with health psychologists are essential for sustainable prenatal mental health care in primary health settings.